2016
DOI: 10.1021/jacs.6b09499
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective, Catalytic Fluorolactonization Reactions with a Nucleophilic Fluoride Source

Abstract: The enantioselective synthesis of 4-fluoroisochromanones via chiral aryl iodide-catalyzed fluorolactonization is reported. This methodology uses HF•pyridine as a nucleophilic fluoride source with a peracid stoichiometric oxidant, and provides access to lactones containing fluorine-bearing stereogenic centers in high enantio- and diastereoselectivity. The regioselectivity observed in these lactonization reactions is complementary to that obtained with established asymmetric electrophilic fluorination protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
59
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(65 citation statements)
references
References 40 publications
4
59
0
2
Order By: Relevance
“…Alkyl, halide, or trifluoromethoxy substitution patterns at the 6‐, 5‐, and 4‐positions of 80 were generally well tolerated, with the fluorolactone products 81 being obtained in 30–96% ee . However, substrates 80 carrying more electron‐deficient trifluoromethyl or carbomethoxy groups led to reduced yields and enantioselectivities (Scheme ) …”
Section: Enantioselective Catalysismentioning
confidence: 99%
“…Alkyl, halide, or trifluoromethoxy substitution patterns at the 6‐, 5‐, and 4‐positions of 80 were generally well tolerated, with the fluorolactone products 81 being obtained in 30–96% ee . However, substrates 80 carrying more electron‐deficient trifluoromethyl or carbomethoxy groups led to reduced yields and enantioselectivities (Scheme ) …”
Section: Enantioselective Catalysismentioning
confidence: 99%
“…In contrast to the established effectiveness of chiral aryl iodide catalysts in enantioselective fluorofunctionalizations of alkenes, 9g,9j,13 only very low levels of enantiocontrol were observed in the corresponding 1,3-difluorination of cyclopropanes such as 1a with a variety of catalysts (see Supporting Information). While the identification of effective chiral catalysts for enantioselective ring-opening difluorination reactions will demand further effort, we found that stereochemically complex 1,3-difluorination products could be accessed effectively with achiral aryl iodide catalysts from readily accessible chiral cyclopropanes.…”
mentioning
confidence: 96%
“…We and others have developed oxidative 1,2-difunctionalization reactions of alkenes based on aryl iodine(I–III) catalysis, 9 and we hypothesized that the alkene-like π-donating properties of unactivated cyclopropanes could give rise to promotion of 1,3-oxidation reactions by similar mechanisms (Figure 1b). Indeed, Szabó and coworkers demonstrated very recently that 1,1-disubstituted cyclopropanes undergo 1,3-difluorination in the presence of stoichiometric iodine (III) reagents together with stoichiometric AgBF 4 .…”
mentioning
confidence: 99%
“…[11] Jacobsen could improve as imilar reaction with fluorine as nucleophile by using metachloroperbenzoic acida so xidant and thereby facilitating a sub-stoichiometrically use of the iodine mediator. [12] We wanted to expand this type of reactionb yu sing electrochemical conditions in order to circumvent the use of stoichiometric amountso fo xidanto ri odine(III) reagent and furthermore by using ad ifferent introduced nucleophile. We chose trifluoroethoxylate as it is achallenging anion due to its low nucleophilicity and furthermore due to itsp otentiala pplication in pharmacologically active compounds.…”
mentioning
confidence: 99%
“…Furthermore,a nI Rd eformation vibration in III and in order to cover steric effects, various Sterimol parameters and finally the distance L O-O between thetwo oxygen atoms in struc-Scheme1.Previouswork on iodine(III)-mediated lactonisation by Fujita [11] and Jacobsen. [12] Figure 1. DOE optimisedreaction conditionsand plot of measured versus predicted yields.…”
mentioning
confidence: 99%